The Role of Promoter-Associated Histone Acetylation of Haem Oxygenase-1 (HO-1) and Giberellic Acid-Stimulated Like-1 (GSL-1) Genes in Heat-Induced Lateral Root Primordium Inhibition in Maize - Zhang, Hao; Yue, Mengxia; Zheng, Xueke; Gautam, Mayank; He, Shibin; Li, Lijia (Frontiers in Plant Science, 2018)
In plants, lateral roots play a crucial role in the uptake of water and nutrients. Several genes such as Zea mays Haem Oxygenase-1 (ZmHO-1) and Giberellic Acid-Stimulated Like-1 (ZmGSL-1) have been found to be involved in lateral root development. In the present investigation, we observed that heat treatment might be involved in the inhibition of lateral root primordium (LRP) formation in maize, accompanied by an increase in global acetylation levels of histone 3 lysine residue 9 (H3K9) and histone 4 lysine residue 5 (H4K5), suggesting that histone modification was related to LRP inhibition. However, Trichostatin A (TSA), an inhibitor of histone deacetylases (HDACs), apparently did not inhibit the LRP formation, revealing that global hyperacetylation might not be the determining factor in the LRP inhibition induced by heat stress. Furthermore, expression of genes related to lateral root development in maize, ZmHO-1 and ZmGSL-1, was down-regulated and the acetylation levels in the promoter region of these two genes were decreased under heat stress, suggesting that promoter-associated histone acetylation might be associated with the expression of ZmHO-1 and ZmGSL-1 genes which were found to be involved in the heat-induced LRP inhibition in maize.